New species of Superodontella Stach, 1949 (Collembola, Odontellidae) from western part of Ukraine - Kaprus, Ighor J.; Weiner, Wanda M. (Zootaxa, 2007)
Three new species of Superodontella from Ukraine are described and illustrated, S. multisensillata, S. huculica and S. ruta. These new species differ in the number of sensilla on antennal segment IV, in the size of mucro and postantennal organ, in the shape of dental setae and in the chaetotaxy of labium.